BACTERIOLOGICAL ISOLATION IN THE RESTAURANT OF HAWLER CITY KURDISTAN REGION, IRAQ - Tablo Abdulrahim Ahmed (Science Heritage Journal)
This investigation was applied to isolate and identify bacteria in three different restaurants order to predict their effects on people. Power plate method for isolation of bacteria the samples were inoculated into nutrient agar media by streak plate technique to obtain well isolated colonies. The results show the identity and the total colony forming units (CFU) for bacteria. The most frequently isolated bacteria were the bacterial species: Bacillus cereus, Clostridium botulinum, Escherichia coli, Salmonella typhi, Shigella dysenteriae, Staphylococcus aureus and Lactobacillus subtilus (11.12, 8.24, 20.11,17.32, 17.01, 10.31 and 8.27) % respectively. According to the bacteria the higher numbers of bacteria were isolated on menu and containers.